Direct Imaging of Weak‐to‐Strong‐Coupling Dynamics in Biological Plasmon–Exciton Systems. Issue 8 (5th June 2022) - Yuan, Zhiyi; Huang, Shih‐Hsiu; Qiao, Zhen; Gong, Chaoyang; Liao, Yikai; Kim, Munho; Birowosuto, Muhammad D.; Dang, Cuong; Wu, Pin Chieh; Chen, Yu‐Cheng
Abstract: Optical coupling plays a pivotal role in nanophotonic systems, which can be divided into weak, intermediate, and strong‐coupling regimes. Monitoring optical coupling strength is, therefore, the key to understanding light–matter interactions. State‐of‐the‐art approaches based on spectral measurements offer the power to quantify and characterize optical coupling strength at a single cavity level. However, it remains challenging to dynamically characterize coupling strength during the transition from strong‐ to weak‐coupling regimes for many systems simultaneously. Here, a far‐field imaging technique is reported that can directly monitor optical coupling dynamics in plasmon–exciton systems, allowing multiple nanocavity emissions to be characterized from weak‐ to strong‐coupling regimes. Light‐harvesting biomolecules—chlorophyll‐a—is employed to study dynamic light–matter interactions in strongly coupled plasmonic nanocavities. Identification of coupling strength is achieved by extracting red, green, and blue (RGB) values from dark‐field images and an enhancement factor from fluorescence images. Lastly, the ability to monitor subtle changes of coupling dynamics in bioplasmonic nanocavity is demonstrated. These findings may deepen the understanding in light–matter interactions, paving new avenues toward applications in quantum‐based biosensing and imaging. Abstract : In this study, a dynamic imaging technique is proposed that can directly monitor optical coupling dynamics in plasmon–exciton systems, allowing multiple nanocavity to be characterized. By employing RGB channels from dark‐field microscopy, subtle changes of biomolecules can be visualized and monitored from weak to strong coupling, offering the possibility of using such a system to characterize biomolecular interactions and activities.